2020
DOI: 10.1136/bmjopen-2020-038741
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of immunological recovery following HAART among severely immunosuppressed patients at enrolment to care in Northern Ethiopia: a retrospective study

Abstract: ObjectiveThis study aimed to identify determinants of immunological recovery following highly active antiretroviral therapy (HAART) among severely immunosuppressed patients at enrolment to care in Northern Ethiopia.MethodsA retrospective study.SettingThe study was done in Tigray Region, Northern Ethiopia.ParticipantsThe study was done among severely immunosuppressed (<200 CD4 cells/mm3) individuals at initial enrolment to care and whose samples were sent for viral load determination from April 2015 to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These OIs might contribute to the decrement of current CD4 + T-cell counts. 53 Moreover, women with advanced HIV status commonly experience a decreased CD4 cell count, and this in turn means the women experience advanced HIV disease, which is at a high risk of death even after starting ART. 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These OIs might contribute to the decrement of current CD4 + T-cell counts. 53 Moreover, women with advanced HIV status commonly experience a decreased CD4 cell count, and this in turn means the women experience advanced HIV disease, which is at a high risk of death even after starting ART. 12…”
Section: Discussionmentioning
confidence: 99%
“…These OIs might contribute to the decrement of current CD4 + T-cell counts. 53 Moreover, women with advanced HIV status commonly experience a decreased CD4 cell count, and this in turn means the women experience advanced HIV disease, which is at a high risk of death even after starting ART. 12 The current study also revealed that women with an initial regimen of first-line ART drugs specifically AZT +3TC+EFV were significantly associated with increased CD4 + T-cell count.…”
Section: Discussionmentioning
confidence: 99%